2016
DOI: 10.1099/jmm.0.000231
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Clostridium difficile diagnostic methods for identification of local strains in a South African centre

Abstract: Accurate diagnosis of Clostridium difficile infection is essential for disease management.A clinical and molecular analysis of C. difficile isolated from symptomatic patients at Groote Schuur Hospital, South Africa, was conducted to establish the most suitable clinical test for the diagnosis and characterization of locally prevalent strains. C. difficile was detected in stool samples using enzyme-based immunoassays (EIA) and nucleic acid amplification methods, and their performance was compared with that of C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…However, CDI is understudied in low and limited resource settings, including nearly all African countries. Where limited data exists, a study at a tertiary hospital in Cape Town, South Africa found 22% of stool samples from patients with suspected CDI diarrhoea were C. difficile positive [2]. In addition, patients in South Africa are disproportionately affected by HIV and tuberculosis (TB) and therefore also experience known CDI risk factors of prior hospital and antibiotic exposure-exposures that can uniquely contribute to an increased risk of CDI and poor outcomes [3,4].…”
Section: Outbreaks Have Been Reported Extensively In Thementioning
confidence: 99%
“…However, CDI is understudied in low and limited resource settings, including nearly all African countries. Where limited data exists, a study at a tertiary hospital in Cape Town, South Africa found 22% of stool samples from patients with suspected CDI diarrhoea were C. difficile positive [2]. In addition, patients in South Africa are disproportionately affected by HIV and tuberculosis (TB) and therefore also experience known CDI risk factors of prior hospital and antibiotic exposure-exposures that can uniquely contribute to an increased risk of CDI and poor outcomes [3,4].…”
Section: Outbreaks Have Been Reported Extensively In Thementioning
confidence: 99%
“…In a study from the Western Cape, SA, researchers attributed a lower CDI burden to strain diversity and low levels of toxin Incidence rate/10 000 days RESEARCH production. [3] In this study, the positivity rate of Xpert (21.13%) was almost double that of EIA (11.41%). Although toxin EIAs are rapid, widely available and inexpensive, they have poor sensitivity and are no longer recommended as stand-alone tests.…”
Section: Research Discussionmentioning
confidence: 47%
“…[9] Studies have shown that toxin EIA tests are less sensitive than PCR and results are variable owing to toxin degradation associated with delayed sample testing. [3] Delayed processing may have contributed to the lower positivity rate in the current study. In a study from the Western Cape, SA, researchers attributed a lower CDI burden to strain diversity and low levels of toxin Incidence rate/10 000 days RESEARCH production.…”
Section: Research Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Because diagnostic tests performed with different reference methods occurred in the same article, 22 independent studies (including 9352 samples) were defined in the meta-analysis. Table 1 shows the characteristics of these included studies [1635]. The prevalence of CDI across all studies ranged from 10% to 47.9%.…”
Section: Resultsmentioning
confidence: 99%